Bimbingan Belajar Matematika Kepada Siswa Kelas IX Di SMP Kristen Payeti, Waingapu, Sumba Timur, NTT - FELIANI ABSASCE MARKUS (Jurnal Pengabdian Barelang, 2019)
Learning tutoring activities for class IX students at SMP Kristen Payeti are a form of community service carried out by Gerakan Mahasiswa Matematika (Gamma) in this case to improve student learning motivation and help teachers guide class IX students to prepare themselves before National exam. The purpose of this activity is seen from the situation analysis conducted that the Mathematics learning process in the class is still not optimal due to several factors such as insufficient time to discuss too many math questions with different levels of difficulty, coupled with the number of students in the class IX which is quite a lot and has minimal teaching staff. This tutoring activity took place very well with a positive response from some students who were very enthusiastic in learning because the learning methods carried out by some counselors were very interesting but the infrastructure in schools was still very minimal so that students' learning motivation was not fully optimal. Tutoring activities as a form of community service are very important to help increase student learning motivation both in class or outside the classroom, and also as a guide is very useful as a form of new experience and closer to the community in this case the school community.